Effect of Inhibition of Angiotensin-Converting Enzyme and/or Neutral Endopeptidase on Neuropathy in High-Fat-Fed C57Bl/6J Mice - Lawrence Coppey; Bao Lu; Craig Gerard; Mark A. Yorek (Journal of Obesity)
We have demonstrated that treating diet-induced obese (DIO) mice with the vasopeptidase inhibitor ilepatril improved neural function. Vasopeptidase inhibitors block angiotensin-converting enzyme (ACE) and neutral endopeptidase (NEP) activity. We propose that increased activity of ACE and NEP contributes to pathophysiology of DIO. To address this issue C57Bl/6J mice or mice deficient in NEP were fed a high-fat diet and treated with ilepatril, enalapril, ACE inhibitor, or candoxatril, NEP inhibitor, using both prevention and intervention protocols. Endpoints included glucose utilization and neural function determination. In the prevention study glucose tolerance was impaired in DIO C57Bl/6J mice and improved with ilepatril or enalapril. Sensory nerve conduction velocity, thermal nociception, and intraepidermal nerve fiber density were impaired in DIO C57Bl/6J mice and improved with ilepatril or candoxatril. In the intervention study only enalapril improved glucose tolerance. Sensory nerve conduction velocity and intraepidermal nerve fiber density were improved by all three treatments, whereas thermal nociception was improved by ilepatril or candoxatril. In NEP-deficient mice DIO impaired glucose utilization and this was improved with enalapril. Nerve function was not impaired by DIO in NEP-deficient mice. These studies suggest that ACE and NEP play a role in pathophysiology associated with DIO.